The Influence of Historical and Cultural Contexts on English Literature: A Contemporary Analysis - Mashuri, mashuri (STIBA IEC JAKARTA, 2025)
From the Middle Ages to the present, this research explores the significant influence of historical and cultural settings on the evolution and interpretation of English literature. This research shows how political upheavals, social movements, technological advancements, and cultural shifts have continuously shaped literary expression, themes, and narrative techniques through a thorough analysis of literary works and their socio-historical backgrounds. In order to demonstrate the dynamic relationship between literature and its contextual environment, the research combines literary criticism, historical analysis, and cultural studies through interdisciplinary approaches. Results show that English literature functions as a mirror reflecting societal values, conflicts, and changes throughout history, in addition to being a medium for artistic expression.